Developing Entrustable Professional Activities for Entry Into Clerkship. (February 2016) - Chen, H. Carrie; McNamara, Margaret; Teherani, Arianne; Cate, Olle ten; O'Sullivan, Patricia
Abstract : Purpose: Despite the growing emphasis on early clinical experiences, preceptors still face challenges integrating preclerkship medical students into their practices. Entrustable professional activities (EPAs), which frame competencies in the context of clinical workplace activities, may provide explicit guidance on appropriate student roles and activities. This study aimed to develop and appraise content validity evidence for EPAs for clerkship entry. Method: The authors employed a multistep process from November 2012 to June 2014. They identified EPA content domains using study data, student focus groups, and preceptor interviews. They then mapped each domain to preclerkship course objectives, graduation competencies, and resident-level EPAs to ensure relevancy and adequacy. Next, they developed seven-part EPA descriptions for each domain with specifications/limitations; expected knowledge, skills, and attitudes; associated competencies; and assessment information. Subsequently, they conducted local, national, and international workshops to verify the appropriateness of the content and supervision level, before finalizing each EPA with additional expert and stakeholder review. Results: This process resulted in five EPAs for entry into clerkship: (1) information gathering, (2) information integration for a differential diagnosis and plan, (3) health care team communication, (4) information sharing with patients, and (5) resource identification. Workshop participants approved and refined the content for each EPA and agreed that a single level of supervision (practice under reactive supervision) was appropriate. Conclusions: The development of these EPAs indicates support for setting a standard for entry into clerkship, provides guidance for engaging preclerkship students in clinical workplace activities, and can be adapted for use by any institution.